2016
DOI: 10.4103/0301-4738.178145
|View full text |Cite
|
Sign up to set email alerts
|

Advances in retinal imaging for diabetic retinopathy and diabetic macular edema

Abstract: Diabetic retinopathy and diabetic macular edema (DME) are leading causes of blindness throughout the world, and cause significant visual morbidity. Ocular imaging has played a significant role in the management of diabetic eye disease, and the advent of advanced imaging modalities will be of great value as our understanding of diabetic eye diseases increase, and the management options become increasingly varied and complex. Color fundus photography has established roles in screening for diabetic eye disease, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 57 publications
(85 reference statements)
1
15
0
Order By: Relevance
“…Larger FAZ areas have been observed in the superficial, deep, and summated capillary plexus in diabetic patients in several studies using OCT angiography (OCTA), which is one of the current retinal imaging methods and allows construction of microvascular flow maps. 24,25,26,27 Also, similar to our study, disorganization and loss of retinal capillaries was observed more precisely in the deep plexus with more severe DME in OCTA images. 28 Although enlargement of the cyst in both planes seems to be associated with macular ischemia, vertical enlargement and retinal thickness had a greater impact on the ischemic process.…”
Section: Discussionsupporting
confidence: 90%
“…Larger FAZ areas have been observed in the superficial, deep, and summated capillary plexus in diabetic patients in several studies using OCT angiography (OCTA), which is one of the current retinal imaging methods and allows construction of microvascular flow maps. 24,25,26,27 Also, similar to our study, disorganization and loss of retinal capillaries was observed more precisely in the deep plexus with more severe DME in OCTA images. 28 Although enlargement of the cyst in both planes seems to be associated with macular ischemia, vertical enlargement and retinal thickness had a greater impact on the ischemic process.…”
Section: Discussionsupporting
confidence: 90%
“…These results indicate that the imaging range of the Optos 200Tx is better than that of the Spectralis. Although the results of the present study suggest that the above two ultra-wide-angle equipment provide a comprehensive display of fundus lesions, including no perfusion area, microangioma, vascular leakage, neovascularization and retinal degeneration, when it comes to the peripheral retina, the Optos 200Tx was indicated to be more capable of displaying the above-mentioned fundus lesions ( 19 ). The Optos 200Tx is able to identify peripheral retinal lesions that are missed by the Spectralis, which is of great value for the guidance of clinical treatments, including laser therapy and intravitreal injection ( 19 ).…”
Section: Discussionmentioning
confidence: 63%
“…Several prospective studies have shown very good correlation between different imaging modalities with UWF imaging. 15 Silva et al 16 have reported UWF imaging increased the identification of DR (38.4% vs 33.8%, P =0.0053) and vision threatening DR (14.5% vs 11.9%) compared to non-mydriatic fundus photography. Moreover, peripheral retinal lesions could be detected located outside the ETDRS 7-standard field in more severe assessment of the level of DR in 9% of patients and neovascularization elsewhere (NVE) which were not seen on ETDRS 7-field photography.…”
Section: Discussionmentioning
confidence: 97%